Comparing The Viral Load of Severe Acute Respiratory Syndrome Coronavirus 2 in Different Human Specimens - Hattem Hussain, Ali (Kurdistan Journal of Applied Research, 2020)
This meta-analysis study analyzed the data of 47 recent studies with data related SARS-COV-2 viral load detection in different human specimens. 1099 patients were tested for SARS-COV-2 viral load using up to 19 different respiratory and non-respiratory specimens using RT-PCR by targeting different types of viral genes of which ORF1ab is the most commonly used target gene. 9909 specimens were taken from the patients. The mean of viral load cycle threshold value is 17.8 (±11.7), with a median of 15.95 with minimum value of 0.2 and a maximum value of 36.5. Nasopharyngeal swab has the highest positivity rate (90.5%) for viral load detection followed by Bronchoalveolar lavage, nasal swab, nasopharyngeal aspirate, throat swab and sputum. For the non-respiratory specimen, stool and rectal swab are most appropriate specimens followed by blood. The urine is not appropriate specimen for viral load detection due to very low sensitivity. The sputum was positive up to 23 days in a daily manner since start of symptoms except for the days 19, 21, and 23 that were negative for the virus. Three specimens, the nasopharyngeal swab, throat swab, and rectal swab, showed positive RT-PCR results before the appearance of COVID-19 clinical features. Possible positive results can be present up to 43 days in throat swab, stool, and rectal swab. After negative conversion of respiratory specimens, the viral shedding can continue more than one month from stool and rectal swab. The 3rd day since onset of symptoms is the most day of testing (223/2935). The highest positivity of SARS-COV-2 viral load was recorded in day 16 since the onset of symptoms.